Uji Aktivitas Antibakteri Ekstrak Etanolik Kayu Secang (Caesalpinia sappan L.) terhadap Staphylococcus aureus - Diah Mukti Cahyaningtyas; Nony Puspawati; Rinda Binugraheni (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2019)
Piogenic infection is an infection characterized by the occurrence of severe local inflammation with pus formation (pus). Generally caused by piogenic germs, one of the most common is Staphylococcus aureus. One of the plants used as an ingredient in traditional medicine and used as an anti-bacterial is a secang plant. This study aims to determine the anti-bacterial activity of ethanolic extract of secang wood (Caesalpinia sappan L.) on pure cultivation Staphylococcus aureus Laboratory and isolates pus Hospital patients and find out the difference in inhibition between the two bacterias.300 grams of secang wood powder was extracted by maceration method using 70% ethanol (1:10). Maserate was used to test the anti-bacterial activity of Staphylococcus aureus from pure cultivation laboratory and isolates of pus patients in hospital using diffusion and dilution methods. Then, the results of the diffusion test were analyzed using a two-way Anova test.The results of the study showed that ethanolic extracts of wood have anti-bacterial activity. Result of dilution method showed the value of KBM at a concentration of 3% for Staphylococcus aureus cultivation Laboratory and a concentration of 4% for Staphylococcus aureus isolates pus patients of the Hospital. The statistical analysis of diffusion test results showed that the best concentration in inhibiting the growth of these two bacterias were the concentration of 25% and the sensitivity of Staphylococcus aureus from Laboratory pure cultivation and the Pus patients isolate of the Hospital toward extracts were the same.